2021
DOI: 10.7759/cureus.13282
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital Versus Lorazepam for Management of Alcohol Withdrawal Syndrome: A Retrospective Cohort Study

Abstract: Introduction Annually, 500,000 episodes of alcohol withdrawal syndrome (AWS) are severe enough to require clinical attention. A symptom-triggered lorazepam regimen remains the standard of care for the management of hospitalized AWS patients. However, phenobarbital has also been shown to be an effective adjunctive therapy for severe AWS, reducing benzodiazepine use in the emergency department (ED) and the intensive care unit (ICU). The purpose of this study is to compare hospital length of stay (LOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…In this study, patients who received phenobarbital had a statistically significant reduced length of stay and lower rates of 30-day readmission. Additionally, there was a trend but not statistically significant for ICU transfer in the phenobarbital group compared to the benzodiazepine group (3.23% compared to 7.04% p=0.1114) [8].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this study, patients who received phenobarbital had a statistically significant reduced length of stay and lower rates of 30-day readmission. Additionally, there was a trend but not statistically significant for ICU transfer in the phenobarbital group compared to the benzodiazepine group (3.23% compared to 7.04% p=0.1114) [8].…”
Section: Introductionmentioning
confidence: 72%
“…In other similar studies [8][9][10][11], there are varied outcomes in relation to ICU admission, intubation and 30-day readmission rates when comparing benzodiazepines and phenobarbital. This study further demonstrates variation in these outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to six studies [18-23], the pooled prevalence of patients who had a history of DT was 27% (CI 0.95, 0.42, I 2 =93%, n=204/778) in the BZD group (Figure 2A) and 30% (95%CI 0.18, 0.43, I 2 =90%, n=182/587) in the PB group (Figure 2B). Five studies [20][21][22][23][24] reported CIWA-AR. The median CIWA-AR score in patients who received BZD was 9.046 plus minus 5.87, and that in patients who received PB was 10.3 plus minus 7.2.…”
Section: Pooled Analysis With Heterogeneitymentioning
confidence: 99%
“…The pooled prevalence of intubation was reported by 5 trials [18, [20][21][22][23] as 4% (95% CI 0.00, 0.12, I 2 = 86%, n=23/359) in the BZD group and 4% (95% CI 0.02, 0.06, I 2 =5%, n=17/444) in the PB group [18] (Figure 7A and 7B). Re-admissions reported in the BZD treatment group were 11.97%, and 9.52% in the PB treatment group [24]. The prevalence of other adjunct medication usage was reported by three trials [18,20,21]…”
Section: Pooled Analysis With Heterogeneitymentioning
confidence: 99%